Racial Microaggression, Overt Discrimination, and Distress: (In)Direct Associations With Psychological Adjustment. (May 2020) - Lui, P. Priscilla
Scholars in diverse disciplines have examined the associations between psychological adjustment and microaggression, and overt discrimination. It remains unclear whether the roles of microaggression in adjustment outcomes can be differentiated from the roles of overt discrimination and neuroticism. I examined the extent to which racial microaggression explained unique variances of negative affect, alcohol consumption, and drinking problems while controlling for overt discrimination and neuroticism among African American, Asian American, and Latinx American college students ( N = 713). Intervening roles of psychological distress linking microaggression and overt discrimination to adjustment outcomes were also tested. Among African Americans, microaggression and overt discrimination did not consistently predict psychological adjustment. Among Asian and Latinx Americans, microaggression and overt discrimination predicted negative affect via psychological distress. Microaggression also explained the variances of alcohol use outcomes among Asian Americans. Findings are discussed in the context of an acute racism reactions model and underscore the importance of considering overt discrimination and microaggression simultaneously as determinants of psychological adjustment.